Fulminant spontaneous autoimmunity of the central nervous system in mice transgenic for the myelin proteolipid protein-specific T cell receptor - Waldner, Hanspeter (The National Academy of Sciences, 2000)
Proteolipid protein (PLP)-139–151 is the dominant encephalitogenic peptide that induces experimental autoimmune encephalomyelitis (EAE) in SJL (H-2(s)) mice. To examine the contribution of T cell receptor (TCR) specificity in the induction of EAE, we generated transgenic mice expressing the rearranged TCR genes from an encephalitogenic or a nonencephalitogenic PLP-139–151/I-A(s)-specific T cell clone. Both types of transgenic lines developed spontaneous EAE, but, remarkably, the lines expressing the TCR from the nonencephalitogenic clone showed increasingly higher frequencies of disease (60–83%) in progressive SJL backcrosses and could not be propagated on the susceptible background. The T cells from the transgenic mice were not tolerized, because they responded vigorously to the antigen in vitro and mediated EAE when the mice were immunized with antigen. Besides being the only description of a TCR transgenic mice for the PLP-139–151/I-A(s) epitope, the results demonstrate that the TCR from a nonencephalitogenic PLP-specific T cell clone can induce autoimmune disease when expressed appropriately in vivo.